Manajemen Pelayanan Manasik Jama’ah Haji Lansia (Studi pada PT. Arafah Raya Gemilang Bengkulu) - Wahnesly Nurliya Anggraini; Supardi Mursalin; Makmur (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine how the management of guidance service for elderly Hajj pilgrims is implemented by PT. Arafah Raya Gemilang Bengkulu. This study used a qualitative method with a case study approach. Data collection techniques were carried out through interviews, observation, and documentation. The research informants consisted of the Deputy Director, Marketing Manager, HRD, and elderly pilgrims who had participated in the guidance activities at PT. Arafah Raya Gemilang Bengkulu. The results of the study indicate that the management of guidance service for elderly Hajj pilgrims has been implemented quite well based on the elements of tangibles, reliability, responsiveness, empathy, and assurance. The company provides adequate facilities to support the guidance activities such as projectors, guidebooks, Kaaba miniatures, and sound systems (loudspeakers). Equal distribution of materials for both attending and absent pilgrims, consistency of schedules, as well as fast, patient, and friendly services for elderly pilgrims can be seen from how the staff greet them politely, smile warmly, and listen without interrupting the pilgrims while speaking. In addition, the services provided are expected to help elderly pilgrims understand the procedures of Hajj worship more easily and comfortably.